Dinamika Teori Penawaran Dalam Menentukan Struktur Harga Dan Output Pasar - khoirun niswah; sri wigati; ahmad azizul muttaqin (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to comprehensively analyze and describe how the dynamics of supply theory influence the structure of market price and output level. The research method adopted is the descriptive-qualitative method, utilizing library research, which involves collecting secondary data from books, scientific journals, and economic reports. The results of this analysis indicate that supply dynamics occupy a central role in the formation of price and market output; therefore, understanding these dynamics can provide extremely valuable insights into how markets function. The key drivers are production costs, technology, government policies, and the resource base, which includes both natural resources and human resources. For producers, marginal cost is a very critical determinant in their supply strategy in an attempt to obtain maximum profit. However, different market structures exhibit different supply mechanisms. In perfect competition, supply is elastic and sensitive to price, whereas in a monopoly, supply tends to be more rigid and controlled by the producer's profit strategy. This change in supply has a direct effect: increasing supply tends to lower the price and increase output, while decreasing supply tends to raise the price and reduce output. With this in mind, it is expected that a more in-depth analysis of market mechanisms can be carried out, which allows for making forecasts of the changes taking place within them.